Higher religiosity and spirituality are associated with ethnic group membership among middle-aged and older adults living with HIV. Issue 1 (16th August 2022) - Delgadillo, Jeremy D.; Campbell, Laura M.; Marquine, Maria J.; Heaton, Anne; Rooney, Alexandra S.; Umlauf, Anya; Jeste, Dilip V.; Moore, David J.; Moore, Raeanne C.
Abstract : Background: HIV is a chronic illness that impacts the lives of more than 1 million people in the United States. As persons living with HIV (PWH) are living longer, it is important to understand the influence that religiosity/spirituality has among middle-aged and older PWH. Objective: Compare the degree of religiosity/spirituality among middle-aged and older PWH and HIV-negative individuals, and to identify demographic, clinical, and psychosocial factors associated with religiosity/spirituality among PWH. Method: Baseline data on 122 PWH and 92 HIV-negative individuals (ages 36-65 years; 61.1% Non-Hispanic White) from a longitudinal study were analyzed for the current study. Recruitment occurred through HIV treatment clinics and community organizations in San Diego. Participants completed questionnaires on religiosity, spirituality, and psychosocial functioning. Independent samples t -tests, Pearson correlations, and multiple linear regression analyses were conducted to test the study objective. Results: No significant differences in religiosity/spirituality were found between PWH and HIV-negative individuals. Demographic and psychosocial variables were unrelated to religiously/spirituality among HIV-negative individuals. Among PWH, multiple linear regression models indicated higher daily spirituality was significantly associated with racial/ethnic minority membership (Hispanic/Latino, African American/Black, or Other), fewer years of estimated duration of HIV, greater social support, and higher grit. Greater engagement in private religious practices was significantly associated with racial/ethnic minority membership and higher social support. Conclusions: For PWH, being a racial/ethnic minority and having higher social support was associated with greater engagement in religious/spiritual practices. Future longitudinal studies should examine whether religion/spirituality impacts well-being across the lifespan among racial/ethnic minority groups of PWH.